People or Property Legal Contradictions, Climate Resettlement, and the View from Shifting Ground - Jerolleman, Alessandra; Marino, Elizabeth; Jessee, Nathan; Koslov, Liz.; Comardelle, Chantel; Villarreal, Melissa; de Vries, Daniel; Manda, Simon; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
This open access book explores the intersection of property law, relocation, and resettlement processes in the United States and among communities that grapple with migration as an adaptation strategy. As communities face the prospect of relocating because of rising seas, policy makers, disaster specialists, and community leaders are scrambling to understand what adaptation pathways are legally possible. While in its ideal application, law functions blindly and without variation, the authors find that legal contradictions come to bear on resettlement processes and place certain communities further in harm$1 (Bs way. This book will unearth these contradictions in order to understand why successful community-based resettlement has presented such a challenge to communities that are experiencing increasing land deterioration as a result of climate change. Alessandra Jerolleman is Associate Professor of Emergency Management, Jacksonville State University, USA. Elizabeth Marino is Associate Professor of Anthropology and Sustainability, Oregon State University, USA. Nathan Jessee is Postdoctoral Environmental Fellow at Princeton University's High Meadows Environmental Institute, USA. Liz Koslov is Assistant Professor in the Department of Urban Planning and the Institute of the Environment and Sustainability at UCLA, USA. Chantel Comardelle, Jean Charles Choctaw Nation, Tribal Secretary and Curator. Melissa Villarreal is a PhD candidate in Sociology at the University of Colorado (CU) Boulder, USA. Daniel de Vries is Associate Professor in Anthropology at the University of Amsterdam, the Netherlands. Simon Manda is Lecturer in International Development at the University of Leeds, UK.s
Part I: Conceptualizing Property and Its Contradictions: A Challenge for Climate Justice -- Chapter 1: Pulling at the Thread -- Chapter 2: Property Law and Its Contradictions -- Part II: Proof of Harm -- Chapter 3: Market Orientation as an Environmental Hazard for Resettling Communities -- Chapter 4: Flood Buyout Relocations and Community Action -- Chapter 5: Displacing a Right to Act Communally within Community Relocation -- Chapter 6: Precarious Possessors and (3z(Bthe Right to (rebuilding) the City(3y (B-- Chapter 7: Interrogating (3z(BJust Compensation(3y (Band Flexibility: Details on the Inadequacy (and Importance) of Voluntary Buyouts for Relocation in Alaska -- Part III: The Legal Framework -- Chapter 8: A Primer of Laws, Legal Concepts, and Tools that Structure Relocation -- Chapter 9: Discretion and the Roles People Play in Interpreting and Applying the Law -- Chapter 10: Concluding Thoughts.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Environmental policy; Emigration and immigration -- Government policy; Environmental Law; America -- Politics and government; Social justice; Environmental Policy; Migration Policy; Environmental Law; American Politics; Social Justice